Carnival Costumes, Trinidad, W.I. - Sobian, C. (Art Photo Studio, Port of Spain, Trinidad, 2009)
A Carnival masquerader dressed as an elaborate clown. Postcard numbered C-32919.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Postcards; Trinidad and Tobago; Carnival--Trinidad and Tobago; Carnival costume--Trinidad and Tobago